ASAP CAIR DARI SABUT KELAPA MUDA SEBAGAI BAHAN PENGGUMPAL TAHU - Sari, Manja; Efendi, Raswen; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aimed to study the characteristic of tofu produced by using young coconut shell liquid smoke as coagulant. This research was experimentally conducted with four treatments dan four replications. The treatment used in this study were AC0 (3% acetic acid), AC1 (1% liquid smoke + 2% acetic acid), AC2 (2% liquid smoke + 1% acetic acid), and AC3 (3% liquid smoke). The results showed that using of young coconut shell liquid smoke as coagulant of tofu significantly affected yield, number of bacteria, ash contents, water contents, protein contents, descriptive sensory test of colour, aroma, and texture, hedonic test of colour and aroma, and hedonic overall test. The selected treatment in this study was AC1 (1% liquid smoke + 2% acetic acid). The tofu had 163.90%yield, 5.4pH, 81.79%water content, 0.15% ash content, 14.30%protein content, and 5.8x105cfu.ml-1 number of bacteria. Sensory characteristic of tofu was white colour, tofu’s characteristical flavor and rather soft texture. Based on hedonic test of colour, aroma, texture, and overall test, the panelists like the tofu. Keywords: tofu, coagulant, liquid smoke, young coconut shell